2016
DOI: 10.1021/acs.jnatprod.5b00932
|View full text |Cite
|
Sign up to set email alerts
|

Variochelins, Lipopeptide Siderophores from Variovorax boronicumulans Discovered by Genome Mining

Abstract: Photoreactive siderophores have a major impact on the growth of planktonic organisms. To date, these molecules have mainly been reported from marine bacteria, although evidence is now accumulating that some terrestrial bacteria also harbor the biosynthetic potential for their production. In this paper, we describe the genomics-driven discovery and characterization of variochelins, lipopeptide siderophores from the bacterium Variovorax boronicumulans, which thrives in soil and freshwater habitats. Variochelins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 62 publications
4
39
0
Order By: Relevance
“…6A). The products of 7 of 9 IβH Asp domains (with the exception of pyoverdine Pf0-1 and variobactin) have reported β-OHAsp stereochemistry, all 3S (29,30,33,34,(51)(52)(53). The target NRPS module of each IβH Asp domain lacks an E domain, thereby producing the L-threo (2S, 3S) configuration of β-OHAsp (Table 1 and Fig.…”
Section: Stereochemistry Of β-Ohaspmentioning
confidence: 99%
See 1 more Smart Citation
“…6A). The products of 7 of 9 IβH Asp domains (with the exception of pyoverdine Pf0-1 and variobactin) have reported β-OHAsp stereochemistry, all 3S (29,30,33,34,(51)(52)(53). The target NRPS module of each IβH Asp domain lacks an E domain, thereby producing the L-threo (2S, 3S) configuration of β-OHAsp (Table 1 and Fig.…”
Section: Stereochemistry Of β-Ohaspmentioning
confidence: 99%
“…Based on homology to SyrP and OrbG, the existence of a number of β-OHAsp residues in siderophores has been rationalized (7,11,(24)(25)(26)(27)(28) or predicted (29)(30)(31)(32)(33). Recently, Kurth et al (33) used cucF, a β-hydroxylase domain from the cupriachelin (Fig. 2) gene cluster, as a handle to scan genomes for photoactive Fe(III)-siderophores, leading to the discovery of variochelin (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…Genome miningh as becomeapowerful method for searching for new bioactive secondary metabolites by using the genome data of bacteria. [7][8][9][10][11][12][13][14][15][16][17] Ah igh percentageo fh alogenase-gene-possessing actinobacteria has been reported to contain polyketide synthase genes and/orN RPS genes, thus indicating the genetica nd physiological potentialo fh alogenases for the productiono fs econdary metabolites, possibly halometabolites. [18] So far,m ore than 4000 halometabolites have been discovered, [19] including commercially important antibiotics, such as chloramphenicol, [20] vancomycin, [21] and teicoplanin.…”
Section: Introductionmentioning
confidence: 99%
“…C, DEPT-135, DQF-COSY,T OCSY,N OESY,H MBC, HSQC, and 1 H-15 NHSQC. In the 1 HNMR spectrum, a-protons of amino acid residues (d = 3.72,3.90, 4.18, 4.38, 4.66, and 4.69 ppm) and amide protons (d = 7.24, 7.29, 7.58, 7.69, 7.77, and 8.33 ppm) were observed.…”
mentioning
confidence: 99%
“…Halomonas, Marinobacter, Ochrobactrum, Synechococcus, and Vibrio [175][176][177][178]. Using a genome mining strategy, Variovorax boronicumulans BAM-48, a plant-associated terrestrial bacterium wasalso found to produce variochelins [151]. These siderophores support the growth of the producing organism by making important nutrients such as iron biologically available to them and also play a crucial role in determining the microbial community structure [179,180].…”
Section: Lipopeptides As Siderophoresmentioning
confidence: 99%